Development and Psychometric Validation of the Cyprus Aphasia Screening Test (CAST) - Charalambous, Marina; Phylactou, Phivos; Kambanaros, Maria (My University, 2025)
Background/Objectives: Aphasia screening tools help healthcare professionals detect aphasia after a stroke. To date, there is no standardized and validated aphasia screening tool available for use in Cyprus. The Cyprus Aphasia Screening Test (CAST) is a newly developed tool for detecting post-stroke aphasia. This study aims to present the main characteristics of the CAST and evaluate its psychometric properties and diagnostic accuracy. Methods: A cross-sectional study was conducted, involving 99 participants divided into three groups as follows: 43 people with stroke-aphasia, 21 with strokes but without aphasia, and 35 healthy controls. Results: The CAST demonstrated excellent internal consistency (Cronbach’s α > 0.967), high test–retest (ICC ≥ 0.983) and interrater (ICC = 0.979) reliability, and verified known-groups validity (p< 0.001). A significant correlation between the total scores of the CAST and the Greek version of the Boston Diagnostic Aphasia Examination (Short Form) confirmed a linear relationship across the two measures (p < 0.001). A ROC curve analysis (AUC = 0.97) identified 36/40 as the cut-off for detecting aphasia. Conclusions: The CAST is a reliable, clinician-administered aphasia screening tool with strong psychometric properties. It is designed to identify post-stroke aphasia and distinguish between stroke patients with and without aphasia. It consists of 10 subtests that assess both language comprehension and production. The CAST is designed for easy scoring and requires minimal equipment, making it well-suited for quick and efficient administration at the bedside. The CAST represents a step forward in aphasia screening for Greek-speaking populations in Cyprus.
Keywords: psychometric testing; stroke; aphasia; screening test